Verbrennungskontrollierte Erwärmung des Brennraums zur Emissionsreduktion während des Kaltstarts - Untersuchungen zu Emissionen und zur Flammenausbreitung - Titus, Fabian (KIT Scientific Publishing, 2019)
This work describes the influence of catalytic converter heating strategies on the emissions during heating operation, as well as during the subsequent load demand at different engine start temperatures. A novel strategy is presented, that provides heating of the combustion chamber, without decreasing the catalyst converter heating significantly. The studies were carried out on a gasoline engine. Emissions were examined in detail. In addition, the flame propagation is evaluated experimentally.